2020
DOI: 10.3390/ijms21176234
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions of 5-Fluorouracil with Inhibitors of Protein Kinase CK2 Correlate with p38 MAPK Activation and FAK Inhibition in the Triple-Negative Breast Cancer Cell Line

Abstract: Background: The combination effect of 5-fluorouracil (5-FU) with either CX-4945 or a new inhibitor of protein kinase CK2, namely 14B (4,5,6,7-tetrabromo-1-(3-bromopropyl)-2-methyl-1H-benzimidazole), on the viability of MCF-7 and triple-negative MDA-MB-231 breast cancer cell lines was studied. Methods: Combination index (CI) values were determined using an MTT-based assay and the Chou-Talalay model. The effect of the tested drug combinations on pro-apoptotic properties and cell cycle progression was examined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT)-based viability assay: after incubation with the test compounds, an MTT test was performed as described previously (Wińska et al, 2020). Optical densities were measured at 570 nm using a BioTek microplate reader.…”
Section: Cell Culture and Treatment Of Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT)-based viability assay: after incubation with the test compounds, an MTT test was performed as described previously (Wińska et al, 2020). Optical densities were measured at 570 nm using a BioTek microplate reader.…”
Section: Cell Culture and Treatment Of Agentsmentioning
confidence: 99%
“…After incubation, the suspension cells were collected by centrifugation at 260 RCF and washed 3 times with ice-cold PBS and supernatants were discarded and pellets were storage at -20 °C up to 1 month. In order to obtain lysates, RIPA buffer (50 mM Tris-HCl pH 7.4, 1% NP-40, 0.5% sodium deoxycholate, 0.1% SDS, 150 mM NaCl, 2 mM EDTA, 50 mM NaF, 0.2 mM sodium orthovanadate, and protease inhibitors cocktail, Roche) was added as it was described elsewhere (Wińska et al, 2020). Adherent monolayer cells were washed three times in ice-cold PBS, and the cells were scraped and lysed in RIPA as it was described previously (Wińska et al, 2020).…”
Section: Western Blottingmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the original research articles, Wińska et al tested the combination effect of 5-fluorouracil (5-FU), with specific inhibitors of protein kinase CK2 in the triple-negative breast cancer cell line. They found that inhibitors of protein kinase CK2 can improve 5-FU-based anticancer therapy and proposed FAK kinase as an attractive target for cancer therapy [ 8 ]. In the next research article, Szoltysek et al focused on DRAK2, a novel stress response kinase that plays a critical role in apoptosis, T-cell biology, and B-cell activation in chronic lymphocytic leukemia (CLL).…”
mentioning
confidence: 99%